2019
DOI: 10.1111/2041-210x.13185
|View full text |Cite
|
Sign up to set email alerts
|

What does a zero mean? Understanding false, random and structural zeros in ecology

Abstract: Zeros (i.e. events that do not happen) are the source of two common phenomena in count data: overdispersion and zero‐inflation. Zeros have multiple origins in a dataset: false zeros occur due to errors in the experimental design or the observer; structural zeros are related to the ecological or evolutionary restrictions of the system under study; and random zeros are the result of the sampling variability. Identifying the type of zeros and their relation with overdispersion and/or zero inflation is key to sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
118
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 36 publications
0
118
0
1
Order By: Relevance
“…In all count models, a negative binomial distribution showed an improved fit over the Poisson distribution, and was therefore chosen as the family. Zero inflation, which assumes a mix of structural and sampling zero data, was initially considered as initial data exploration revealed a high proportion of zeros in the data, which can indicate zero inflation, or overdispersion relative to the Poisson distribution [55]. However, we did not find sufficient reason to consider zeros as structural, and zero inflation tests in DHARMa (function: ‘testZeroInflation()’) did not show statistical support that data were zero-inflated.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…In all count models, a negative binomial distribution showed an improved fit over the Poisson distribution, and was therefore chosen as the family. Zero inflation, which assumes a mix of structural and sampling zero data, was initially considered as initial data exploration revealed a high proportion of zeros in the data, which can indicate zero inflation, or overdispersion relative to the Poisson distribution [55]. However, we did not find sufficient reason to consider zeros as structural, and zero inflation tests in DHARMa (function: ‘testZeroInflation()’) did not show statistical support that data were zero-inflated.…”
Section: Methodsmentioning
confidence: 85%
“…Variation in snail counts was analysed using generalized linear mixed effect models (GLMM) in the package glmmTMB [54]. This package efficiently fits negative binomial models that can account for overdispersed count data, while also allowing for arguments to account for zero inflation, if needed [55]. The fit of all constructed models was investigated visually and statistically using a simulation-based approach in the package DHARMa [56].…”
Section: Methodsmentioning
confidence: 99%
“…A high proportion of plots exhibited no recruits for a given species (e.g., 70% for Leptecophylla tameiameiae and 80% for Coprosma ochracea ), resulting in zero inflation (i.e., an excess of zeros in comparison to those expected from a classical count probability distribution). This can entail biased parameter estimates, overestimation of standard errors, and result in the selection of excessively complex models and poor ecological inference (see Blasco‐Moreno, Pérez‐Casany, Puig, Morante, & Castells, ). To avoid zero inflation, we grouped recruits according to their dispersal syndrome.…”
Section: Methodsmentioning
confidence: 99%
“…We also observed that over 40% of the articles in our dataset were never cited ( Fig. 1a), but since these represent "true zeros" 36 we didn't apply zero-inflated models to infer citation patterns over time 37 . No collinearity was detected among the seven explanatory variables-all |r|< 0.7.…”
Section: Relationship Between Citations and Reference List Characterimentioning
confidence: 96%